Вычислить<span>
1.) (tg60</span>°-tg30° )/( 1+tg60°*tg30°)=(√3-1/√3)/{1+√3·(1/√3)}=[(2√3)/3]/2=√3/3
<span>
2) 4sin^2(75</span>°)*cos^2(75°)-(sin^2(75°)-cos^2(75°<span>))^2=
=(2</span>sin(75°)*cos(75°))²-(-cos(2·75°)²=(sin(2·75°))²-(-cos(2·75°)²=(1/2)²-(√3/2)²=
=1/4-3/4=-1/2
<span>
</span>
5с - 100%
8с - 70%
7с - 50%
100+70+50=220
220/3=73.3% вероятность правильного ответа
64 меньше 80 а 80 меньше 91. 254 меньше 255 а 255 меньше 256. 304 меньше 381 а 381 меньше 392. 99 меньше 100 а 100 меньше 101.